2022
DOI: 10.1140/epjp/s13360-022-03305-2
|View full text |Cite
|
Sign up to set email alerts
|

A study of potential laser-induced degradation in remote standoff Raman spectroscopy for wall paintings

Abstract: A mobile remote standoff Raman spectroscopy system operational at typical distances of 10 m was developed specifically for research of historical sites and wall paintings recently. Here we present an upgrade to that system informed by a thorough experimental investigation of the relevant laser-induced degradation issues. Reflectance spectroscopy as a more sensitive technique than Raman spectroscopy was used for monitoring and a new phenomenon of reversible alterations was detected in many paint samples at very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…This technique starts also to be used for cultural Heritage studies. 9,[89][90][91] The two sets of spectra were visually similar, supporting the potential use of a handheld Raman spectrometer with stand-off attachment for blood detection at the scene of crime.…”
Section: Mobile Instrumentationmentioning
confidence: 61%
See 3 more Smart Citations
“…This technique starts also to be used for cultural Heritage studies. 9,[89][90][91] The two sets of spectra were visually similar, supporting the potential use of a handheld Raman spectrometer with stand-off attachment for blood detection at the scene of crime.…”
Section: Mobile Instrumentationmentioning
confidence: 61%
“…Finally, Almehmadi and Lednev 79 collected bloodstain spectra using a handheld Raman spectrometer equipped with a standoff attachment and compared with spectra acquired with a benchtop Raman microscope. This technique starts also to be used for cultural Heritage studies 9,89–91 . The two sets of spectra were visually similar, supporting the potential use of a handheld Raman spectrometer with stand‐off attachment for blood detection at the scene of crime.…”
Section: Novelty Of the Approachesmentioning
confidence: 71%
See 2 more Smart Citations
“…16 Our recent studies found that the two commonly employed inspection techniques, visual observation and Raman monitoring, are also not sensitive enough to detect some short-term alterations on paints that can be detected only with visible and near infrared (VIS-NIR) reflectance spectroscopy. 6,17,18 Although visual inspection and Raman spectroscopy can offer useful guidance for the detection of certain laser-induced damages, they can be blind to physical changes (e.g., partial melting of the surface) and inter and intra molecular scale damage below the detection limit. In some cases, the alteration may not correspond to damage of the pigment (e.g., alteration in the binding medium).…”
Section: Introductionmentioning
confidence: 99%